HUBUNGAN TIPE KEPRIBADIAN DENGAN MANAJEMEN STRES DALAM PENYUSUNAN SKRIPSI - Farida Hayati; Dina Zakiyyatul Fuadah; Kiki Maelani (Jurnal EDUNursing, 2023)
Personality type is one of the factors that influence the emergence of stress. Stress is a condition that arises as a result of a mismatch between the demands received and the ability to overcome them, which is often encountered among students during the thesis preparation process. Good stress management is needed by students to avoid the various negative effects of stress they experience. The purpose of this study was to determine the relationship between personality types and stress management in the preparation of the undergraduate thesis of Nursing Study Program Stikes by Husada Kediri. The research design is correlational with a cross sectional approach. The population was 108 students, 32 samples were obtained by purposive sampling technique. Data collection used a questionnaire Based On Jung's Type Indicator Test for personality types and a stress management questionnaire. The results showed that almost all respondents (87.5%) had an extrovert personality type. Meanwhile, almost all respondents (87.5%) have high stress management. The results of the chi square statistical test obtained (p-value) of 0.00 < 0.05 with r:1,000 (perfect correlation) with a positive relationship direction, meaning that if students have an extroverted personality type and have high stress management, strategies for managing stress are good with perfect relationships obtained from personality type questionnaire data where almost all respondents have a good depth of thinking in writing thesis and almost all respondents dare to take risk in the preparation of the thesis. It is expected that students with extroverted personality types can limit and control themselves so that in carrying out an activity it can be useful. Keywords: Personality type, Stress management, Thesis